2008
DOI: 10.1016/j.neulet.2008.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Trait cheerfulness modulates BOLD response in lateral cortical but not limbic brain areas—A pilot fMRI study

Abstract: Having a good "sense of humor" is an important personality characteristic that significantly influences social communication and may represent an important coping strategy. To take things "with humor" does not only represent a state characteristic but also a personality trait that can reliably be assessed with questionnaires like the "state-trait-cheerfulness-inventory" (STCI) by Ruch [Ruch et al., Assessing the "humorous temperament": construction of the facet and standard trait forms of the statetrait-chee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Eisenberger et al (2005) observed a positive correlation in a more rostral ACC locus during an oddball paradigm, which is less demanding than are three-back working memory tasks. Using emotional-motivational tasks (e.g., emotional Stroop, emotion induction), most studies showed a positive correlation (e.g., Canli et al, 2004;Canli et al, 2001;Haas et al, 2006;Keightley et al, 2003; for a negative correlation, see Fruehholz et al, 2010;Rapp et al, 2008). During resting state, positive (e.g., Ebmeier et al, 1994;Sugiura et al, 2000), as well as negative (e.g., Hermes, 2007), associations were detected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eisenberger et al (2005) observed a positive correlation in a more rostral ACC locus during an oddball paradigm, which is less demanding than are three-back working memory tasks. Using emotional-motivational tasks (e.g., emotional Stroop, emotion induction), most studies showed a positive correlation (e.g., Canli et al, 2004;Canli et al, 2001;Haas et al, 2006;Keightley et al, 2003; for a negative correlation, see Fruehholz et al, 2010;Rapp et al, 2008). During resting state, positive (e.g., Ebmeier et al, 1994;Sugiura et al, 2000), as well as negative (e.g., Hermes, 2007), associations were detected.…”
Section: Discussionmentioning
confidence: 99%
“…c Approximating and projecting peak activations (x-coordinates for all peaks within X ± 1 cm) from prior positron emission tomography (PET; Johnson et al, 1999;Keightley et al, 2003), single photon emission computed tomography (SPECT; Sugiura et al, 2000), continuous arterial spin labeling (CASL; Hermes, 2007), and functional magnetic resonance imaging studies (fMRI; Canli et al, 2004;Canli et al, 2001;Eisenberger et al 2005;Fruehholz et al 2010;Gray & Braver, 2002;J. R. Gray et al, 2005;Haas et al, 2006;Kumari et al, 2004;Rapp et al, 2008) investigating extraversion effects under resting conditions (circles), while emotional/motivational tasks (triangles) and cognitive tasks (squares) were performed, on the sagittal slice of the present LORETA solution running through the BA 24 peak voxel (MNI-coordinates x = 4, y = 31, z = 22). For all studies, sample size, the extraversion scale employed, and the direction of the extraversion-ACC relation (+ = positive correlation; -= negative correlation) are provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, many neuroimaging studies have examined the neural substrates involved in humor comprehension (Bekinschtein et al, 2011;Chan et al, 2012aChan et al, , 2012bFranklin and Adams, 2011;Dolan, 2001, 2007;Marinkovic et al, 2011;Mobbs et al, 2003Mobbs et al, , 2005Moran et al, 2004;Neely et al, 2012;Rapp et al, 2008;Samson et al, 2009Samson et al, , 2008Vrticka et al, 2013aVrticka et al, , 2013cWatson et al, 2007;Wild et al, 2006). These studies can be classified into two main groups based on the stimulus modalities used in the experiments: visual and verbal.…”
Section: Introductionmentioning
confidence: 99%
“…It seems more likely, therefore, that the greater importance of right-than left-hemisphere prefrontal-posterior (de-)coupling in the present results is related to the processing of social-emotional information rather than to cognitive processes implicated in the perception of humor (cf. Rapp et al, 2008).…”
Section: Discussionmentioning
confidence: 99%